2017
DOI: 10.1038/nri.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells in homeostasis and host defence of epithelial barrier tissues

Abstract: Epithelial surfaces line the body and provide a critical interface between the body and the external environment which is essential to maintaining the symbiotic relationship between the host and the microbiome. Tissue-resident epithelial γδ T cells represent a major T cell population in epithelia and are ideally positioned to perform barrier surveillance and aid in tissue homeostasis and repair. In this review we focus on the intraepithelial γδ compartment in the two largest epithelial tissues in the body, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
328
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(353 citation statements)
references
References 145 publications
11
328
0
2
Order By: Relevance
“…In mice, γδ T cells have been increasingly recognized as contributing to both innate and adaptive immune responses (33)(34)(35). During development, murine γδ T cells leave the thymus, possess invariant TCRs, and populate various epithelial sites in tissues and organs (33)(34)(35), such as the Vγ5 + γδ T cells in mouse epidermis (40).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, γδ T cells have been increasingly recognized as contributing to both innate and adaptive immune responses (33)(34)(35). During development, murine γδ T cells leave the thymus, possess invariant TCRs, and populate various epithelial sites in tissues and organs (33)(34)(35), such as the Vγ5 + γδ T cells in mouse epidermis (40).…”
Section: Discussionmentioning
confidence: 99%
“…While γδ T cells represent only a small fraction of T cells in the circulation or lymphoid tissues, they form a substantial tissue‐resident population at epithelial and mucosal barrier sites and are therefore likely influenced by the intestinal microbiota. Some tissues contain highly restricted or specialized γδ T‐cell populations, such as Vγ5 + T cells, that are exclusively found in the intestinal epithelium . It has been demonstrated that the microbiota can induce IL‐17A‐producing γδ T cells in diverse tissues such as the skin, liver, oral cavity, eyes, lungs and intestinal epithelium …”
Section: The Impact Of the Intestinal Microbiota On Memory T‐cell Popmentioning
confidence: 99%
“…Their localization puts γδ T cells at the frontline for surveillance, and they are able to respond rapidly to damage and infection, helping mediate their repair, secreting antimicrobial peptides, and coordinating the escalation of the immune response if necessary through cytokine/chemokine production. The functions and contributions of γδ T cells to immune responses have been well-reviewed in a number of excellent articles (911). Here, we will focus our discussion on the repertoire landscape of γδ T cells to try and highlight the emerging pattern whereby the γδTCR seemingly directs cell-fate decisions in a clonotypic-manner.…”
Section: The γδ T Lymphocyte the Founding Member Of The Unconventionmentioning
confidence: 99%
“…A number of invariant γδTCR clonotypes have been discovered across multiple species, and in each case a public, easily-generated γδTCR commits the developing T cell to a discrete fate and localization within specific tissues (mucosa, lymphoid organs, dermis) (16). This provides a useful mechanism for sorting different subsets of γδ T cells to their intended tissue where they establish residency and provide surveillance and response in tune with the tissues requirements.…”
Section: The γδ T Lymphocyte the Founding Member Of The Unconventionmentioning
confidence: 99%